Reinventing leadership making the connection between politics and business - Kellerman, Barbara (Albany, N.Y State University of New York Press, 1999)
In a striking departure from past practices, Barbara Kellerman explores the fact that although we persist in viewing political and business leadership separately, the similarities between them far outweigh the differences. Kellerman claims that thinking of government and corporate leaders as a breed apart contributes to the dysfunctional gap between them, and she argues that in order to tackle those political, economic, and social problems that are the most intractable, political and business leaders will have no choice but to work together.
Includes bibliographical references (p. 233-252) and index.
Keywords: Leadership